Whose story is this? : old conflicts, new chapters - Solnit, Rebecca (Haymarket Books, 2019)
Who gets to shape the narrative of our times? The current moment is a battle royale over that foundational power, one in which women, people of color, non-straight people are telling other versions, and white people and men and particularly white men are trying to hang onto the old versions and their own centrality. In Whose Story Is This? Rebecca Solnit appraises what's emerging and why it matters and what the obstacles are.